Heterogeneity of motivations among crowdinvestors: Evidence from the football industry - Szczepan Kościółek (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: As the issue of the motivations of crowdinvestors is still heavily debated, empirical research has come to focus on specific industries and the heterogeneity of motivations within specific crowdfunding models. This study combines these two perspectives and considers the research question of the heterogeneous motivations of football club crowdinvestors. The aim of the study is to segment the football club crowdinvestors according to investment motivations. METHODOLOGY: In this study, the survey research method was used for a sample (n = 793) of crowdinvestors from the Wisla Krakow football club, and a two-step motivation-based segmentation approach was applied. The convenient sampling method was used as the club distributed the surveys electronically among all its crowdinvestors in July 2021. A cluster analysis, including Ward’s method with Euclidian distance and the non-parametric k-means method, was applied to segment the market. Differences between segments were assessed with chi-square tests for qualitative variables and Kruskal-Wallis H tests with Dunn’s post hoc tests for quantitative variables. A discriminant analysis successfully validated the segmenting procedure. FINDINGS: The crowdinvestors of football clubs were divided into three market segments: benefit-oriented (50.7%), club-oriented (45.3%), and goal-oriented (4.0%). This clustering solution was influenced by all of the previously identified motivations: fan identification, supporting a campaign’s cause, status of football club owner, rewards, and return on investment. The segments were also differentiated according to consumption-related behaviors (media consumption, word-of-mouth marketing, merchandise purchases, match attendance, and social media engagement) and socio-demographic profiles (age, marital status, income, and place of residence). With the exception of the goal-oriented niche, crowdinvestors of football clubs are fans who are highly identified with the club and focused on supporting the cause of the campaign. However, some of them (“benefit-oriented”) are more sensitive than others to the return on investment, rewards, and status that comes along with club ownership (“club-oriented”). Benefit-oriented crowdinvestors consume the club’s products to the greatest extent, while goal-oriented crowdinvestors are on the opposite side of the spectrum. IMPLICATIONS: Based on self-determination theory, no cluster with a predominance of extrinsic motivations was found. These results are in opposition to most crowdfunding studies, but are in line with sport management literature. Importantly, evidence was found showing that groups that are homogenous in terms of crowdinvestment activity can still be heterogeneous in terms of crowdinvestment motivations. This insight shows that crowdinvestment motivations should be considered in more detail than they have been in the past. The assumptions of the multi-needs-meeting phenomenon of crowdinvesting in football clubs were also confirmed. These outcomes provide sports managers with information about market segments of crowdinvestors that they can use to communicate their crowdfunding campaigns more effectively. ORIGINALITY AND VALUE: This study is the first to present the research-tested heterogeneity of investment motivations among football club crowdinvestors. It shows the instability of research results that focus on entire crowdfunding models and ignore the industry-related specificities and internal diversity of crowdinvestors. Moreover, it extends the area of research on fan investors in the football industry, which has, until this point, focused on investment motivations without taking their internal heterogeneity into account.